Authority and Accountability: Policy Innovation through Evaluation Institutionalization in Gulf States - Anis Ben Brik (17413672) (2025)
Institutionalizing evaluation represents a critical form of policy innovation, yet literature on evaluation in authoritarian contexts remains sparse. This study investigates how Gulf Cooperation Council states have institutionalized evaluation as policy innovation, addressing three fundamental questions: how monarchical governments institutionalize continuous learning and adaptation, how centralized political regimes structure incentives for evaluation innovation, and how the risks and benefits of evaluation policy innovation are distributed across actors. Through systematic analysis of 78 policy documents across six Gulf countries, this research reveals the distinctive characteristics of authoritarian policy innovation: strategic alignment with national development visions, prevalence of implicit policy structures, establishment of specialized institutions under centralized oversight, and emphasis on performance measurement serving legitimacy-building functions. The findings identify a hybrid governance model integrating new public management principles, digital capabilities, and traditional monarchical authority. This approach enables systematic policy learning while managing political risks through controlled processes. Despite successful institutional embedding, the study reveals tensions between authority and technical capabilities and genuine accountability mechanisms. This study advances policy innovation theory by demonstrating how non-democratic regimes structure unique incentives through legitimacy-seeking rather than electoral accountability, institutionalize learning within bounded parameters preserving centralized control, and distribute benefits asymmetrically – concentrating technical improvements among governing elites while minimizing accountability risks. These findings expand understanding of policy innovation processes beyond democratic contexts, revealing how authoritarian regimes can pursue innovation while preserving core power arrangements. Other Information Published in: Journal of Comparative Policy Analysis: Research and Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13876988.2025.2549022